An elegant woman : [large type] a novel - McPhee, Martha (Wheeler Publishing, a part of Gale, a Cengage Company, 2020)
"Drawn from the author's own family history, this is a story of discovery and reinvention, following four generations of women in one American family. As Isadora, a novelist, and two of her sisters sift through the artifacts of their forebears' lives, trying to decide what to salvage and what to toss, the narrative shifts to a winter day in 1910 at a train station in Ohio. Two girls wait in the winter cold with their mother--the mercurial Glenna Stewart--to depart for a new life in the West. Framed by Isadora's efforts to retell her grandmother's journey, the novel is an evocative exploration of the stories we tell ourselves, and what we leave out."--Back cover.